Reconstruction of Sports Dispute Settlement Law Through Integrated Sports Dispute Settlement - Goncalwes Sirait; Adi Mansar; Farid Wajdi (Faculty of Law, Universitas Pekalongan, 2025)
Sport is a strategic asset in fostering national integration and strengthening social capital due to its inherently democratic nature, prioritizing brotherhood even amidst intense competition on the field. The fundamental values ​​that often save a nation from disunity are deliberation and consensus, and problems in sport are ideally resolved through deliberation and consensus in accordance with true wisdom. In essence, civil disputes are resolved peacefully by seeking agreement between the disputing parties. Because disputes arise from conflicting personal interests, their resolution depends heavily on the initiative of the parties involved. Civil disputes can be resolved either conventionally through the courts (litigation) or using alternative dispute resolution methods outside the courts. Dispute resolution through the courts is subject to provisions of civil procedural law, such as the Herzienne Indonesisch Reglement (HIR) for the Java and Madura regions, the RBg (Rechtsreglement Buitengewesten), and other regulations governing civil procedure. Courts serve as a means of law enforcement, a place of legal protection, and a forum for citizens involved in disputes to seek justice. Current practices for resolving disputes regarding competitive sports are not fully in line with Article 102 of Law Number 11 of 2022 concerning Sports, which states that disputes in sports must be resolved through deliberation and consensus by the parent sports organization. If deliberation and consensus cannot be reached, the disputing parties must enter into a written agreement regarding the chosen dispute resolution method. Dispute resolution is carried out through mediation, conciliation, and arbitration